2021
DOI: 10.1016/j.landurbplan.2021.104255
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling associations between vegetation greenness and dengue in a Latin American city: Findings and challenges

Abstract: Highlights Vegetation greenness is negatively but insignificantly associated with dengue incidence. This association is stronger in socioeconomically vulnerable areas. Improved vegetation quality has the potential to reduce dengue risk. Openly accessible, coarse resolution environmental data have limitations in environmental health studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 68 publications
0
4
0
1
Order By: Relevance
“…Our study found a negative association between vegetation factors and dengue incidence rates in general ( Figure 1 (A3–B3) and Figure 2 (A3–B3)). Vegetation factors included NDVI, which is a measure of vegetation that combines the impact of vegetation quantity, including its coverage and biomass, and quality [ 30 ], as well as total vegetation area, forest cover, managed vegetation cover, and grass cover. The negative association between vegetation cover and dengue transmission is consistent with previous studies [ 31 , 32 ] that have shown that variables such as farm, forest, and grassland have significant negative correlations with dengue transmission and can provide a protective barrier against Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found a negative association between vegetation factors and dengue incidence rates in general ( Figure 1 (A3–B3) and Figure 2 (A3–B3)). Vegetation factors included NDVI, which is a measure of vegetation that combines the impact of vegetation quantity, including its coverage and biomass, and quality [ 30 ], as well as total vegetation area, forest cover, managed vegetation cover, and grass cover. The negative association between vegetation cover and dengue transmission is consistent with previous studies [ 31 , 32 ] that have shown that variables such as farm, forest, and grassland have significant negative correlations with dengue transmission and can provide a protective barrier against Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Colocam ainda que os mosquitos urbanos que preferem recipientes artificiais de água para oviposição; e foi encontrado uma relação positiva em ambientes de telhado de amianto e solo exposto (que os mosquitos preferem habitar). No estudo realizado por Cunha et al, (2021b) a associação dengue-verde foi modificada por fatores socioeconômicos, sendo encontrada uma associação positiva entre casos de dengue e vegetação em localidades com maior vulnerabilidade socioeconômica, e uma associação negativa em regiões com menor vulnerabilidade social, o que pode ser confirmado neste estudo.…”
Section: Resultsunclassified
“…In recent years, a rise in global temperature has been observed, mainly caused by the increase in the emission of gases that produce the greenhouse effect, along with an rampant deforestation in different ecosystems [46,47]. In Belo Horizonte, natural and preserved green areas protect socioeconomically vulnerable communities against the occurrence of dengue fever [13].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, anthropogenic factors such as deforestation and poor sanitarian conditions also favors the population dynamics of this arbovirus. Aedes aegypti is uncapable to invade native forests, and in cities it adapted to lay eggs and develop in any small pots, taking advantage of garbage and urban untreated trashes [11][12][13]. For instance, Cunha et al [12] identified that preserved native forests close to neighborhoods under great socio-economic vulnerability in a large Brazilian city, functioned as a barrier against the occurrence of dengue.…”
Section: Introductionmentioning
confidence: 99%